2006
DOI: 10.1606/1044-3894.3565
|View full text |Cite
|
Sign up to set email alerts
|

Building Secure Relationships: Attachment in Kin and Unrelated Foster Caregiver–Infant Relationships

Abstract: The attachment relationships of 46 infants with their kin and unrelated foster caregivers are reported in the results of this study. Secure attachment relationships were found in about equal percentages in kin and unrelated caregiver-infant dyads (67-68%), similar to the percentage of secure attachment relationships found in birth and adoptive caregiver-infant dyads in previous studies. Disorganized/disoriented attachment behaviors were observed in a greater percentage of kin and unrelated foster caregiver-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 48 publications
(58 reference statements)
2
34
0
Order By: Relevance
“…The continuous outcome was used in two studies (Belanger 2002;Davis 2005). Length of placement was measured continuously by length of stay in the kin or foster placement in five studies (Berrick 1994;Brooks 1998;Cole 2006;Davis 2005;Surbeck 2000) and continuously by length of total stay in out-of-home care in five other studies (Belanger 2002;Clyman 1998;Jenkins 2002;Sivright 2004;Tompkins 2003). It should be noted that longer lengths of stay in placement or in care are considered negative outcomes in the U.S., as reunification within 12 months is the primary permanency goal for children placed in short-term kinship or foster care.…”
Section: Placement Stabilitymentioning
confidence: 99%
“…The continuous outcome was used in two studies (Belanger 2002;Davis 2005). Length of placement was measured continuously by length of stay in the kin or foster placement in five studies (Berrick 1994;Brooks 1998;Cole 2006;Davis 2005;Surbeck 2000) and continuously by length of total stay in out-of-home care in five other studies (Belanger 2002;Clyman 1998;Jenkins 2002;Sivright 2004;Tompkins 2003). It should be noted that longer lengths of stay in placement or in care are considered negative outcomes in the U.S., as reunification within 12 months is the primary permanency goal for children placed in short-term kinship or foster care.…”
Section: Placement Stabilitymentioning
confidence: 99%
“…Kinship foster caregivers were significantly less likely than non-relative foster caregivers to report desire to increase family size and express concerns for the community. Another study (Cole 2006) investigated the attachment relationships of 46 infants placed in both kinship and non-kin foster care. Findings from the study indicate that a majority of both kin and non-kinship caregiver-infant dyads equally exhibited secure attachment behaviors.…”
Section: Attachmentmentioning
confidence: 99%
“…There has been important, though limited, work on the relationship between foster youth and their caregivers. The importance of the quality of the relationship between infants and toddlers in foster care and their caregivers has been elevated by a number of researchers (Cole, 2006; Harden, 2007; Harden & Klein, 2011; Spieker, Oxford, Kelly, Nelson, & Fleming, 2012). Studies of the alliance/relationship between caregivers and youth in treatment foster care have demonstrated that positive relationships between foster parents and youth are critically important for achieving desired emotional and behavioral outcomes among emotionally disturbed youth in out-of-home care (Bickman et al, 2004; Chamberlain, 2003; Kazdin, Marciano, & Whitley, 2005; Rauktis et al, 2005; Shirk & Karver, 2003; Southerland, Mustillo, Farmer, Stambaugh, & Murray, 2009).…”
Section: Introductionmentioning
confidence: 99%